Longitudinal clinical and proteomic diabetes signatures in women with a history of gestational diabetes - Heaseung Sophia Chung; Lawrence Middleton; Manik Garg; Ventzislava A. Hristova; Rick B. Vega; David Baker; Benjamin G. Challis; Dimitrios Vitsios; Sonja Hess; Kristina Wallenius; Agneta Holmäng; Ulrika Andersson-Hall (JCI Insight, 2025)
We characterized the longitudinal serum protein signatures of women 6 and 10 years after having gestational diabetes mellitus (GDM) to identify factors associated with the development of type 2 diabetes mellitus (T2D) and prediabetes in this at-risk post-GDM population, aiming to discover potential biomarkers for early diagnosis and prevention of T2D. Our study identified 75 T2D-associated serum proteins and 23 prediabetes-associated proteins, some of which were validated in an independent T2D cohort. Machine learning (ML) performed on the longitudinal proteomics highlighted protein signatures associated with progression to post-GDM diabetes. We also proposed prognostic biomarker candidates that were differentially regulated in healthy participants at 6 years postpartum who later progressed to having T2D. Our longitudinal study revealed T2D risk factors for post-GDM populations who are relatively young and healthy, providing insights for clinical decisions and early lifestyle interventions.